Two types of generalized Wiebull distributions and their applications under different enviromental conditions - Al-Mutairi, Dhaifalla Khalid; Agarwal, Satish Kumar (Statistica, 1999)
Two types of generalized Wiebull distributions (G.W.D.) which can be used to describe environmental conditions are suggested along with their statistical properties. Some well known probability distributions which have found applicability under different environmental conditions are shown to the members of family of (G.W.D.). It is shown that the resulting distribution is beta of the second type if the unknown environment condition follows a gamma distribution and the lifelength distribution of a biological specie/component is a type two (G.W.D.).